Application of spatial analysis in assessing the effect of coastal land reclamation and development on seagrass Halophila ovalis and Halophila becarrii distributions in Penang waters - Abdullah, Anisah Lee; Anscelly, Anastacia Amanda (2015)

(untitled)
The aim of this study is to ascertain the possible effects of coastal land reclamation and development on existing seagrass spatial distribution of Halophila ovalis and Halophila beccarii surrounding a man-made islet within Penang waters. The hypothesis was that coastal land reclamation and development has a negative effect on existing seagrass distribution and density. The ArcGIS 10 spatial analysis tools, Standard Deviational Ellipse (SDE) and Standard Distance (SD), were applied to determine phase shifts as an indicator of possible effect of coastal land reclamation on the seagrass distribution. Seagrass shoot densities data used were from year 2003, 2006 and 2009; where 2003 and 2006 represented pre-coastal development period, while 2009 represented on-going coastal development period. Results showed SDE of seagrass experienced shifts from west to north-west direction from 2003 to 2009, which is away from the coastal land reclamation site. In addition, SD result showed seagrass distribution in the islet had shifted from west to east, and was more compacted and concentrated in 2009. The shifts of seagrass mean centre from west to the east also coincided with SD analysis where the largest distance value of 28.21m calculated from centroid occurred in 2009. The shifts in seagrass SDE, SD and mean centres strengthened the hypothesis that the coastal land reclamation and development had a negative effect on seagrass spatial distribution and density in Penang waters. The directional trend, compactness and mean centre of seagrass observed to be directed away and concentrated further from the coastal development site by 2009.